Administration of aspirin tablets using a novel gel-based swallowing aid: an open-label randomised controlled cross-over trial. Issue 4 (4th July 2019) - Wright, David John; Potter, John F; Clark, Allan; Blyth, Annie; Maskrey, Vivienne; Mencarelli, Giovanna; Wicks, Sarah O; Craig, Duncan Q M
Abstract : Introduction: To ease administration of medicines to people with dysphagia we developed and patented a gel formulation within which whole tablets could be inserted. The aim was to determine whether the gel would affect bioequivalence of uncoated aspirin tablet. Method: A gel containing gelatin, hydroxypropylmethylcellulose, citric acid, potassium sorbate and water was developed to maintain structure on tablet insertion and increase saliva production to lubricate the swallow. In an open-label cross-over trial 12 healthy male volunteers were administered a 300 mg uncoated aspirin tablet with and without gel with a 7-day washout period. Blood salicylate levels, platelet activity and patient satisfaction were measured over 2 hours. Analysis was based on a random effects cross-over model. Results: The estimated mean ratio (90% CI) of effect on salicylate levels when comparing administration with and without gel was 0.77 (90% CI 0.40 to 1.47) for amount absorbed and 0.76 (90% CI 0.44 to 1.31) and on total ASP-arachidonic acid platelet activity 1.16 (90% CI 0.88 to 1.53) and maximum ASP-arachidonic platelet activity 0.98 (90% CI 0.79 to 1.22). These results are outside of the range allowable for the assumption of bioequivalence. Participants rated the taste of aspirin tablets significantly better when encapsulated in the gel (p<0.05). Discussion: We cannot assume that uncoated aspirin administration with and without gel is bioequivalent. Administration with gel resulted in reduced salicylate levels and therefore increased platelet function. Further research is required to determine the exact reason for this result. The results bring into question current processes for providing marketing authorisation for medical devices which are designed to aid swallowing.